Influence of pillar plants in vegetation patches on soil carbon in hyperarid ecosystems of the AlUla region - Oscar Pascal Malou; Stéphane Boivin; Baptiste Kerfriden; David Sebag; Jérôme Nespoulous; Ines Ben Ammar; Hassan Boukcim; Yassine Fendane; Sami D. Almalki; Shauna K. Rees; Abdalsamad Aldabaa; Ahmed H. Mohamed; et al. (Journal of Arid Environments, 2026)

Vegetation Increases CH 4 Emissions and Methanotroph Diversity in Marine Sediments - Marion Dolivet‐Maréchal; Carlos Palacin‐Lizarbe; Henri M. P. Siljanen; Dhiraj Paul; Abigaïl Delort; Jonathan Gervaix; Charline Creuzé des Châtelliers; Sabine Schmidt; Mathis Cognat; David Sebag; Olivier Taugourdeau; Clara Schübert; et al. (Global Change Biology, 2026)
Seagrass meadows are key blue carbon (C) ecosystems, storing large amounts of organic C over centuries. Their climate benefits may be reduced by methane (CH 4 ) emissions, whose microbial and environmental descriptors in Zostera noltii meadows, dominant seagrass in North‐Western Europe, remain poorly understood. We studied CH 4 fluxes, CH 4 ‐producing and consuming microbial communities and sediment physicochemical parameters in Z. noltii meadows and adjacent bare sediments across seven sites in Arcachon Bay, France. In situ CH 4 fluxes were measured at low tide during daytime conditions, providing standardized estimates of peak emissions. Microbial communities were characterized using targeted metagenomics of three functional genes ( mcrA , mmoX , pmoA ) and quantitative PCR. CH 4 fluxes were higher in vegetated than bare sediments (24.4 ± 2.6 vs. 9.4 ± 0.7 μmol m −2 day −1 ). Mixed linear models and random forest analyses identified C accumulation rate and CO 2 flux as the strongest positive descriptors of CH 4 fluxes. Vegetated sediments hosted more diverse methanotrophs, while methanogens showed no habitat differences. Four genera ( mcrA–Methanolobus , mmoX–Methylocella , pmoA–Methylococcus , Methyloglobulus ) emerged as abundant, seagrass‐associated, correlated with CH 4 fluxes, and highlighted by models. Functional diversity, especially pmoA richness, was a stronger microbial descriptor of CH 4 fluxes than gene abundance or a specific genus. Findings indicate Z. noltii meadows enhance C burial and CH 4 emission, with methanotroph diversity potentially mitigating CH 4 emissions. Our results provide the first integrated assessment of CH 4 fluxes and their descriptors in Z. noltii meadows, based on limited temporal coverage capturing the daytime peak emission conditions, highlighting the intertwined nature of C burial and CH 4 emissions and the need to account for both in blue C climate assessments.

Environmental and climatic evolution of a river-proximal peatland in the Cuvette Centrale, Congo Basin - Johanna Menges; David Sebag; Judicael Lebamba; Chris Kiahtipes; Hans-Peter Wotzka; Johannes Preuß; Ferdinand Bokomba Bwamangele; Roger Kidebua Lutonadio; Melanie Guardiola; Thierry Adatte; Yannick Stroobandt; Steven Bouillon; et al. (Quaternary Science Reviews, 2025)

Sensitivity to climate and vegetation dynamics of a peatland record from central Cameroon during the African Humid Period - Valentine Schaaff; Vincent Grossi; Matthew Makou; Yannick Garcin; Pierre Deschamps; Bruno Hamelin; Christopher A. Kiahtipes; David Sebag; Benjamin Ngounou Ngatcha; Guillemette Ménot (Quaternary Science Reviews, 2025)

A source-to-sink perspective of an anthropogenic marker: A first assessment of microplastics concentration, pathways, and accumulation across the environment - Sébastien Rohais; John J. Armitage; Maria-Fernanda Romero-Sarmiento; Jean-Lou Pierson; Vanessa Teles; Daniela Bauer; Cyril Cassar; David Sebag; Marie-Hélène Klopffer; Maxime Pelerin (Earth-Science Reviews, 2024)

Constraints on hopanes and brGDGTs as pH proxies in peat - Valentine Schaaff; Vincent Grossi; Matthew Makou; Yannick Garcin; Pierre Deschamps; David Sebag; Benjamin Ngounou Ngatcha; Guillemette Ménot (Geochimica et Cosmochimica Acta, 2024)

Reproducibility of Rock-Eval® thermal analysis for soil organic matter characterization - Lorenza Pacini; Thierry Adatte; Pierre Barré; Mohammed Boussafir; Nicolas Bouton; Lauric Cécillon; Violaine Lamoureux-Var; David Sebag; Eric Verrecchia; Adrien Wattripont; François Baudin (Organic Geochemistry, 2023)

Measuring the stability of soil organic carbon in Arenosols in the Senegalese Groundnut Basin - Oscar Pascal Malou; Tiphaine Chevallier; Patricia Moulin; David Sebag; Murielle Nancy Rakotondrazafy; Ndeye Yacine Badiane-Ndour; Abou Thiam; Lydie Chapuis-Lardy (Journal of Arid Environments, 2023)

Termite constructions as patches of soil fertility in Cambodian paddy fields - Ratha Muon; Pinnara Ket; David Sebag; Hanane Aroui Boukbida; Pascal Podwojewski; Vincent Hervé; Vannak Ann; Pascal Jouquet (Geoderma Regional, 2023)

Modeling the decomposition signal and correcting bulk organic data from a peat deposit, a case study at low latitudes (Cameroon) - Valentine Schaaff; David Sebag; Matthew Makou; Vincent Grossi; Ingrid Antheaume; Bruno Hamelin; Yannick Garcin; Benjamin Ngounou Ngatcha; Pierre Deschamps; Guillemette Ménot (Organic Geochemistry, 2023)

Combining Rock-Eval® thermal analysis and thermochemolysis to evaluate the influence of forest management on soil organic matter quality and stability - Zheng Sun; Katell Quénéa; Frédéric Delarue; Christelle Anquetil; Herman Ravelojaona; David Sebag; Loic Eon; Isabelle Kowalewski (Organic Geochemistry, 2023)

Substrate availability and not thermal acclimation controls microbial temperature sensitivity response to long‐term warming - Luiz A. Domeignoz‐Horta; Grace Pold; Hailey Erb; David Sebag; Eric Verrecchia; Trent Northen; Katherine Louie; Emiley Eloe‐Fadrosh; Christa Pennacchio; Melissa A. Knorr; Serita D. Frey; Jerry M. Melillo; et al. (Global Change Biology, 2023)
Microbes are responsible for cycling carbon (C) through soils, and predicted changes in soil C stocks under climate change are highly sensitive to shifts in the mechanisms assumed to control the microbial physiological response to warming. Two mechanisms have been suggested to explain the long‐term warming impact on microbial physiology: microbial thermal acclimation and changes in the quantity and quality of substrates available for microbial metabolism. Yet studies disentangling these two mechanisms are lacking. To resolve the drivers of changes in microbial physiology in response to long‐term warming, we sampled soils from 13‐ and 28‐year‐old soil warming experiments in different seasons. We performed short‐term laboratory incubations across a range of temperatures to measure the relationships between temperature sensitivity of physiology (growth, respiration, carbon use efficiency, and extracellular enzyme activity) and the chemical composition of soil organic matter. We observed apparent thermal acclimation of microbial respiration, but only in summer, when warming had exacerbated the seasonally‐induced, already small dissolved organic matter pools. Irrespective of warming, greater quantity and quality of soil carbon increased the extracellular enzymatic pool and its temperature sensitivity. We propose that fresh litter input into the system seasonally cancels apparent thermal acclimation of C‐cycling processes to decadal warming. Our findings reveal that long‐term warming has indirectly affected microbial physiology via reduced C availability in this system, implying that earth system models including these negative feedbacks may be best suited to describe long‐term warming effects on these soils.

Polar pesticide contamination of an urban and peri-urban tropical watershed affected by agricultural activities (Yaoundé, Center Region, Cameroon) - Perrine Branchet; Emmanuelle Cadot; Hélène Fenet; David Sebag; Benjamin Ngounou Ngatcha; Valérie Borrell-Estupina; Jules Remy Ndam Ngoupayou; Ives Kengne; Jean-Jacques Braun; Catherine Gonzalez (Environmental Science and Pollution Research, 2018)

Biocontrolled soil nutrient distribution under the influence of an oxalogenic-oxalotrophic ecosystem - Sophie Pons; Saskia Bindschedler; David Sebag; Pilar Junier; Eric Verrecchia; Guillaume Cailleau (Plant and Soil, 2018)

Biodiversity and conservation genetics research in Central Africa: new approaches and avenues for international collaboration - Nicola M. Anthony; Patrick Mickala; Katharine A. Abernethy; Christiane Atteke; Pulchérie Bissiengou; Michael W. Bruford; Francisco Dallmeier; Thibaud Decaëns; Akaibe Dudu; Adam Freedman; Mary Katherine Gonder; Olivier Hardy; et al. (Conservation Genetics Resources, 2012)